2012
DOI: 10.1002/term.1505
|View full text |Cite
|
Sign up to set email alerts
|

Initial immune reaction and angiogenesis in bone healing

Abstract: During hematoma formation following injury, an inflammatory reaction ensues as an initial step in the healing process. As granulation tissue matures, revascularization is a prerequisite for successful healing. The hypothesis of this study was that scarless tissue reconstitution in the regenerative bone healing process is dependent on a balanced immune reaction that initiates revasculatory steps. To test this hypothesis, cellular composition and expression profiles of a bone hematoma (regenerative, scarless) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
132
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(140 citation statements)
references
References 30 publications
6
132
0
2
Order By: Relevance
“…Immune cells are a source of soluble factors, like cytokines, which have angiogenic effects [62], and recruitment capabilities towards other cells, namely MSC [19]. Nair and colleagues have shown that stem cells, namely MSC, can be recruited after biomaterial implantation in a sub-cutaneous mouse model and that cell recruitment may be inhibited by an anti-inflammatory drug [63].…”
Section: Discussionmentioning
confidence: 98%
“…Immune cells are a source of soluble factors, like cytokines, which have angiogenic effects [62], and recruitment capabilities towards other cells, namely MSC [19]. Nair and colleagues have shown that stem cells, namely MSC, can be recruited after biomaterial implantation in a sub-cutaneous mouse model and that cell recruitment may be inhibited by an anti-inflammatory drug [63].…”
Section: Discussionmentioning
confidence: 98%
“…Considering importance of osteoporosis in the individual's activity and increased risk of pathological fractures in the future, determining prevalence and risk factors of the problem in children with type 1 DM and necessary treatments for its reduction is essential (13). Previous studies showed that type 1 DM causes reduction of bone density and ossification markers and increasing bone loss markers, and BMD is a good indicator for detecting changes in bone quality (14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…This type results in graft/ cell rejection. In contrast, in the type II response, the type II T helper lymphocytes trigger macrophage type II activity, which is a remodeling reaction that causes graft/cell acceptance in the body [Schmidt-Bleek et al, 2014;Moshiri et al, 2015a, b]. Recent investigations have shown that allogeneic MSCs promote the polarization of monocytes into an anti-inflammatory M2 phenotype.…”
Section: Mscs and Immunomodulatory Effectsmentioning
confidence: 99%